Does the St. Jude Regent 17‐mm Offer Better Outcomes Than the Hemodynamic Plus 17‐mm Aortic Valve Mechanical Prothesis?. Issue 11 (7th October 2015) - Prifti, Edvin; Bonacchi, Massimo; Baboci, Arben; Giunti, Gabriele; Esposito, Giampiero; Kajo, Efrosina; Nuellari, Edmond; Vanini, Vittorio
Abstract: Objective: The aim of the present study is to report the early and mid‐term clinical and hemodynamic results of a prospective trial investigating the clinical performance of the St. Jude Medical Regent 17 mm (SJMR‐17) versus St. Jude Medical Hemodynamic Plus 17 mm (SJMHP‐17). Materials and Methods: Between January 2000 and August 2013, 20 patients (Group I) with aortic valve (AV) stenosis underwent first time AV replacement with a SJMR‐17 and nine patients (Group II) underwent AV replacement with a SJMHP‐17. The mean follow‐up was 58 ± 31 months. Results: There was one death in Group I. The end‐diastolic IVS thickness and end‐systolic posterior left ventricle (LV) wall thickness was reduced significantly in boths groups (p = 0.001 and p = 0.006 in Group I and p = 0.007 and p = 0.011 in Group II). The peak and mean transprosthesis gradients (P‐TPG and M‐TPG) were 29 ± 6.8 mmHg and 17.5 ± 4.5 mmHg in Group I, significantly lower than in Group II (55.2 ± 19.7 mmHg and 28.8 ± 7.7 mmHg). The postoperative left ventricular mass (LVM) and indexed left ventricular mass (LVMi) were reduced significantly in both groups versus the preoperative values. The postoperative LVMi was 114.5 ± 10.6 g/m 2 in Group I versus 127 ± 8 g/m 2 in Group II (p = 0.01). With dobutamine, heart rate, left ventricular ejection fraction, cardiac output, transprosthesis peak, and mean gradients increased significantly in both groups, however, the P‐TPG and M‐TPG were significantly higher in Group II (p = 0.026 and p = 0.022) despite a non‐significant increase of the indexed effective orifice area. Conclusions: The SJMR‐17 can be employed with satisfactory postoperative clinical and hemodynamic outcomes in patients with small aortic annulus, especially in elderly patients offering better outcome than SJMHP‐17.